Malaria Pigment Crystals: The Achilles′ Heel of the Malaria Parasite - Kapishnikov, Sergey (ChemMedChem, 2021)
The biogenic formation of hemozoin crystals, a crucial process in heme detoxification by the malaria parasite, is reviewed as an antimalarial drug target. We first focus on the in‐vivo formation of hemozoin. A model is presented, based on native‐contrast 3D imaging obtained by X‐ray and electron microscopy, that hemozoin nucleates at the inner membrane leaflet of the parasitic digestive vacuole, and grows in the adjacent aqueous medium. Having observed quantities of hemoglobin and hemozoin in the digestive vacuole, we present a model that heme liberation from hemoglobin and hemozoin formation is an assembly‐line process. The crystallization is preceded by reaction between heme monomers yielding hematin dimers involving fewer types of isomers than in synthetic hemozoin; this is indicative of protein‐induced dimerization. Models of antimalarial drugs binding onto hemozoin surfaces are reviewed. This is followed by a description of bromoquine, a chloroquine drug analogue, capping a significant fraction of hemozoin surfaces within the digestive vacuole and accumulation of the drug, presumably a bromoquine–hematin complex, at the vacuole's membrane.